A rare cause of dyspnea: Isolated congenitally corrected transposition of the great arteries (Annals of Medical Research, 2021)
Corrected transposition of the great arteries is a rare pathology with an incidence of 1% among the congenital heart diseases.It is thought to have multifactorial inheritance. It is mostly seen in men. If there is no concomitant pathology, the blood flow isphysiological and does not show symptoms until advanced ages. Life expectancy is close to normal in those with isolated pathology.Risk factors determining mortality include progressive right ventricular dysfunction, AV block, and severe tricuspid insufficiency. Inthis case, we present a CCTGA patient with dyspnea symptoms without any additional pathology.